A New Paradigm of Land Registratiton Services in Indonesia in The Era of The Industrial Revolution 4.0 and Society 5.0 - Ikhsan Lubis; Tarsius Murwadji; Sunarmi Sunarmi; Detania Sukarja; Tengku Keizerina Devi Azwar (Randwick International of Social Science Journal, 2022)
This study aims to describe the new paradigm of land registration services in Indonesia in the era of the industrial revolution 4.0 and society 5.0. It is time for the government to start being literate in technology that can be used in the implementation of land registration and is urgently needed in thecurrent digitalization era and of course making it easier for the community. The penelitian method used in this study is a qualitative method with a descriptive approach. In this study, the data obtained such as observation results, interview results, shooting results, document analysis, field notes, compiled by researchers at the research site, were not poured in forms and figures. The results showed thatin the face of the industrial revolution 4.0, thegovernment has issued Presidential Regulation Number 95 of 2018 concerningelectronic-based governance systems as the legal basis for its implementation. Article 1 (1) explains that the Electronic-Based Government System (SPBE) is a government administration that utilizes information and communication technology to provide services to SPBE users. The transformation towards the digital era is also carried out on land documents which are one of the supporting factors in the implementation of land administration in the modern era.